The arrival of Homo sapiens into the Southern Cone at 14,000 years ago - Politis, Gustavo Gabriel (2016)
The Arroyo Seco 2 site contains a rich archaeological record, exceptional for South America, to explain the expansion of Homo sapiens into the Americas and their interaction with extinct Pleistocene mammals. The following paper provides a detailed overview of material remains found in the earliest cultural episodes at this multi-component site, dated between ca. 12,170 14C yrs B.P. (ca. 14,064 cal yrs B.P.) and 11,180 14C yrs B.P. (ca. 13,068 cal yrs B.P.). Evidence of early occupations includes the presence of lithic tools, a concentration of Pleistocene species remains, human-induced fractured animal bones, and a selection of skeletal parts of extinct fauna. The occurrence of hunter-gatherers in the Southern Cone at ca. 14,000 cal yrs B.P. is added to the growing list of American sites that indicate a human occupation earlier than the Clovis dispersal episode, but posterior to the onset of the deglaciation of the Last Glacial Maximum (LGM) in the North America.